Perceptions of Relational Mobility Among University Students. - Majeed, Fatima Ali; Jasem, Ahmed Lateef (Journal of Posthumanism, 2025)
This study aims to examine individuals’ perceptions of their relational mobility, that is, how they perceive their interactions and the development of their social relationships. Perceptions of relational mobility are considered central in social psychology, as they reflect an individual's ability to build an effective social network and move flexibly within it, allowing for positive interaction with their social environment. This ability is a fundamental requirement for achieving psychological and social balance, especially in societies undergoing rapid transformations in patterns of interaction and communication.Certain aspects of relational mobility such as low social support, reduced face-to-face communication, and feelings of rejection or loneliness indicate that social relationships are not a luxury but a necessity of human life. Through them, the fabric of daily life is formed, and feelings of belonging, safety, and support are built. People with healthy and balanced relationships tend to be happier, live longer, and are more resilient to life's challenges. Thus, understanding perceptions of relational mobility and their impact plays a vital role. Their importance has grown with the changes brought about by the digital age, where interactions have become faster, shallower, and more prone to change and disconnection. Individuals lacking positive perceptions of their relational mobility may experience social isolation or rejection, leading them to seek compensation through digital platforms (Valkenburg & Peter, 2007).Relational mobility is also a significant indicator of an individual’s capacity for social adaptation, particularly during critical life stages such as adolescence or the transition to university or professional life. Those with positive perceptions of their ability to build and expand their social networks are more capable of handling stress and demonstrate greater competence in managing social tensions (Helsen et al., 2000).